Communicating with parents - Pritchard, Micheal; Elkind, David; Sweet, Freddy; Elkind & Sweet Communications, Inc.; Live Wire Video Publishers (San Francisco : Live Wire Video Publishers, 1988)
Through probing dialogue and hypothetical situations, teen counselor Pritchard and high school students examine some of the ways in which family communication gets blocked, and consider what kinds of choices they can make to improve the situation.
Executive producer, David Elkind, Freddy Sweet ; writers, Steve Most...[et al.] ; editor, yasha Aginsky
Featuring : Micheal Pritchard
Keywords: Parent and child; Communication in the family; Interpersonal relations; Interpersonal communications; Parenting